Analisis Kualitas Sinyal Menggunakan G-Nettrack Pro di Kota Malang - Dania Sartika Anggraeni; Aisah Aisah; Abdul Rasyid (Jurnal Jaringan Telekomunikasi, 2020)
Currently, wireless telecommunication networks (wireless) have developed very rapidly. To meet the demands of today's mobile users for data rate transfer and data services. The application of LTE technology has been intensively carried out in several countries, including Indonesia. The problem that is often faced is the limited coverage area of ??the Base Transceiver Station (BTS) so that not all areas can be covered by the 4G network. Based on this background, this thesis will analyze the performance and signal quality of LTE networks in Malang City. This measurement is done using the G-Nettrack Pro application and the parameters to be measured in this study are RSRQ, RSRP, SINR and Throughput. The location of eNodeB used for research is in 2 Districts in Malang City. From the measurement results of the drive test, it was found that the area of ??Sawojajar and Malang City had a max RSRP value of -64 dBm, a min RSRP of -105 dBm, an average RSRP of -83.2 dBm in the Very good category. RSRQ max -6 dB, min RSRQ -11 dB, and average RSRQ -10.05 dB in the Normal category. SINR max 25 dB, SINR min -3 dB, and SINR average 9.65 dB in the Good category. Uplink max 14546 kbps, Uplink min 0, and an average Uplink 19.96 kbps in the Very bad category. Downlink max 15564 kbps, Downlink min 0, and downlink average 28.6 kbps in the Very bad category.